Background factors for chronic low back pain resistant to cognitive behavioral therapy - Keisuke Shimizu (Nature Portfolio, 2021)
Abstract This study examined the factors that inhibit the therapeutic effects of cognitive behavioral therapy (CBT) and clarify the adaptation judgment criteria of CBT. We included patients with chronic low back pain and allocated them to the adaptation (with visual analog scale [VAS] improvement) or non-adaptation group (without VAS improvement). The patients were analyzed using various psychological tests. CBT improved depressive symptoms and catastrophic thinking; however, they were not correlated with the VAS and did not directly affect low back pain improvement. The non-adaptation group showed an unexplainable/vague sense of anxiety; an excessive focus on searching for pain; a strong intimacy desire; a strong tendency of medical dependency; and fantasy or distortion of the actual experience, especially self-image. Moreover, the patients showed a low ability to objectively express or attribute meaning to pain due to poor language skills, attention-deficit hyperactivity disorder, and emotional value judgment. Individuals with the aforementioned characteristics of pre-CBT psychological tests should select a different treatment approach given the high poor-adaption possibility. Even patients with depressive or anxious symptoms are not necessarily adaptable for CBT. Therefore, pre-CBT tests for treatment suitability are necessary. Future studies should establish a protocol for psychotherapy suitable for the non-adaptation group.